Satire in the Stories of Hassan Ghezelji’s Laugher of the Beggar - Hawkar Mohammad Rashid (پژوهشنامه ادبیات کردی, 2021)
Most of the literary works contain a message, and the poets and writers try to convey the message in different ways to impress their readers. Hassan Ghezelji, the Kurdish writer, sought to express the message through using a unique, concise, and influential technique: satire. He attempted to inform the society of undesirable events through his satirical stories. This study aims to investigate satire and its presentation in Hassan Ghezelji's collection of stories Laughter of the Beggar. Apart from the introduction and conclusion, this research consists of two parts. The first part focuses on the concept and definition of satire in literature and the second part eaddresses the role of satire in Kurdish literature. Then, the role of satire in Ghezelji's stories in Laughter of the Beggar has been practically investigated. Finally, the significant results and findings are presebted.